Необходимость эффективной передачи знаний и навыков работников при помощи автоматизированной обучающей системы для алмазообрабатывающих предприятий (Путеводитель предпринимателя)
It is shown that for diamond processing manufactories experience is a most important factor in providing competitiveness. The concepts of proficiency, knowledge, skill, experience, human capital, intellectual capital are proposed. Relationships between them are shown.